(untitled) (Historia, 2021)
Should History be a compulsory subject in High School in all standards up to Std. X? The ideal position would be for History to be an optional subject freely and willingly chosen by all pupils because, having enjoyed what has been described as a "spacious and leisurely" presentation in the lower standards, they have come to realise that a knowledge of history is valuable for the future citizen and indispensable for the cultured person. For has not History been described as man’s memory, and a bulwark for civilization? "Not to know what happened before we were born," wrote Cicero more than two thousand years ago, "is to remain perpetually a child. For what is the worth of human life unless it is woven into the life of our ancestors by the records of history?"